Analysis of Tax Incentives, Risk Taking and R&D Investment: Evidence Based on Manufacturing - Qiu, Qiaoying (International Journal of Global Economics and Management, 2024)
Although China is a big manufacturing country, its manufacturing industry is "big but not strong". In recent years, in order to encourage manufacturing enterprises to invest resources in innovation projects, preferential tax policies and government subsidies have become important regulatory means. However, due to the different risk bearing capacity of enterprises, enterprises also have different attitudes toward research and development (R&D) investment. In order to test the relationship between the four, this paper takes listed manufacturing companies in China from 2015 to 2020 as samples to empirically analyze the impact of tax incentives on R&D investment, as well as the mediating and moderating effects of risk bearing capacity and government subsidies between them. The results show that tax incentives can significantly promote R&D investment; The risk bearing capacity of enterprises plays a partial mediating role between tax incentives and R&D investment. Government subsidies play a positive regulating role between tax incentives and R&D investment.